2009
DOI: 10.1016/j.physleta.2009.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Exact solution of the Klein–Gordon equation in the presence of a minimal length

Abstract: We obtain exact solutions of the (1 + 1) dimensional Klein Gordon equation with linear vector and scalar potentials in the presence of a minimal length. Algebraic approach to the problem has also been studied.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…In contrast, conditionally exact solutions are generated only for specific values of the potential parameters and for quasi-exact solutions, only part of the energy spectrum is determined. Exact solutions of the Dirac equation in the presence of different potentials were obtained in the past [2][3][4][5] using various theoretical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, conditionally exact solutions are generated only for specific values of the potential parameters and for quasi-exact solutions, only part of the energy spectrum is determined. Exact solutions of the Dirac equation in the presence of different potentials were obtained in the past [2][3][4][5] using various theoretical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In relativistic equations, the minimal length was introduced in the Dirac equation, with a constant magnetic field [22,23], with vector and scalar linear potentials [24], for the hydrogen atom potential [25], and the Dirac oscillator [26,27]. The effect of the GUP was also investigated in the context of the Klein-Gordon equation [22,28,29]. Finally, the Casimir effect [30,31], and the black body radiation [32] have been studied within this modified formalism of quantum mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…For various types of potentials, such as linear, exponential, Coulomb, Rosen-Morse, etc., the exact bound state solutions of the one-dimensional Klein-Gordon equation have been reported. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] It is also reported that the onedimensional Klein-Gordon equation can be exactly solved for shape invariant potentials.…”
Section: Introductionmentioning
confidence: 99%
“…(22). But using the method for finding the superpotential of shape invariant potentials suggested by Cooper and Ginocchio, 31 one may obtain the superpotential W(x) and consequently the ground state effective energy E 1,0 .…”
mentioning
confidence: 99%